The Use of the Quantum Teaching Method to Improve Learning Outcomes of the Al-Qur'an and Hadith Subject for Class IX.6 Students - Amri, An'nisa Miranti (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: The purpose of this study was to determine the learning outcomes of the Al-Qur'an Hadith of class IX.6 students before using the quantum teaching method, the learning outcomes of the Al-Qur'an Hadith of class IX.6 students after using the quantum teaching method, and the differences in learning outcomes of class IX.6 students before and after using the quantum teaching method. Methodology: The type of research used was Pre-Experimental with a One Group Pre-Test - Post-Test design. The sample of this research was class IX.6 as an experimental class totaling 25 students without a control class. Main Findings: The study concluded that student learning outcomes before using the quantum teaching method were in the "very low" category. Student learning outcomes after using the quantum teaching method showed an increase in learning outcomes. There was a significant difference between the scores before and after using the quantum teaching method. Novelty/Originality of this study: The novelty in this study is the use of the Quantum Teaching Method which can Improve Learning Outcomes of the Qur'an and Hadith Subjects in Grade IX Students. This is because there has never been a similar study before which makes this study something new and a new reference for readers and further research who want to study the quantum teaching method in the subjects of the Qur'an and Hadith.